Fostering Healthy Family Relationships: Overcoming Toxic Parents in the Qur'an - Suprapto, Suprapto (EDUCATIO : Journal of Education, 2024)
This study explores the concept of "toxic parents" from the perspective of the Al-Qur'an, offering comprehensive solutions grounded in Islamic teachings. Using a qualitative research method, it generates descriptive data presented in verbal form. The qualitative approach includes data collection through observation, interviews, and document analysis, focusing on real-life experiences and contextual understanding. Furthermore, the study employs the tafsir maudu‘i (thematic interpretation) method to systematically analyze Qur'anic verses related to parent-child relationships. The tafsir maudu‘i method involves identifying relevant themes, gathering pertinent Qur'anic verses, and conducting contextual analysis, incorporating historical backgrounds, reasons for revelation (asbabun nuzul), as well as classical and contemporary interpretations. This approach enables an in-depth exploration of Islamic principles addressing "toxic" behaviors in parenting. The results from the qualitative analysis reveal recurring themes and patterns in the data, highlighting key behaviors and attitudes that constitute "toxic parenting." The thematic interpretation of the Qur'anic verses provides a cohesive understanding of the Islamic perspective on maintaining healthy and ethical family relationships. The study concludes that the Al-Qur'an offers valuable guidance for preventing and addressing "toxic" parental behaviors, emphasizing the importance of compassion, justice, and ethical conduct in fostering harmonious family dynamics.